The Development of Thai Literature Learning Achievement in “The Royal Guidance” Using Cooperative Learning Integrated Reading and Composition (CIRC) Technique for Matthayomsuksa 3 Students - Klamthap, Khanittha; Witchayapakorn, Kanchana (Ratchaphruek Journal, 2020)
The purposes of the research were 1) to compare the students’ learning achievement in Thai Literature entitled “the Royal Guidance” of Mathayomsuksa 3 students by using Cooperative Learning Integrated Reading and Composition (CIRC) technique before and after learning; and 2) to study the students’ satisfaction of learning management. The sample consisted of 39 Mathayomsuksa 3 students at Khaosai Thapklo Phittaya School, Phichit province, in the second semester, academic year2019. The research instruments were lesson plans, the literature achievement test, and the student satisfaction evaluation form. Data were analyzed by mean, standard deviation and t-test (Dependent Samples). The findings of the research were that: The students’ learning achievement in “the Royal Guidance” of Mathayomsuksa 3 using Cooperative Integrated Reading and Composition (CIRC) technique after the learning was higher than at the statistically significant .05 level; The student satisfaction was overall at the high level.